CLINICAL CHARACTERISTICS AND X-RAY IMAGES OF THE MAXILLARY SINUS FRACTURES IN 31 PATIENTS WITH MIDFACIAL TRAUMA - Le Manh Cuong; Phan Hung Phuc; Nguyen Ngoc Anh (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to describe some clinical and radiographic characteristics of MSFs patients at the Department of Maxillofacial and Plastic Surgery, the Military Hospital 103. Methods: Prospective, cross-sectional descriptive study. Results: The mean age of patients was 32.14 ± 13.18; male/female ratio = 5.2/1. The main cause of maxillary sinus fractures was traffic accidents. Common clinical symptoms: sharp pain, swelling in cheekbones, upper jaw, nose bleed (100%); loss of continuity of the maxillary zygomatic arch (70.9%); limited mouth opening (80.6%); numbness in cheeks, nose, upper lip (67.7%); limited eye movement, double vision, reduced visual acuity (6.4%). Most patients broke 3 walls of the maxillary sinus (93.6%). Computed tomography scan helps to accurately and fully detect broken walls of the maxillary sinuses and other lesions in the maxillofacial region, helping to choose the right treatment method.